A wastewater purification composite material supported on loofah sponge and PCN-WO3 heterostructure and its preparation method
Patent Information
- Application Number
- CN202610798581.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-04
- Publication Date
- 2026-09-22
AI Technical Summary
但是,天然植物多孔材料的孔道形貌、孔径分布及结构规整度难以实现精准调控,在一定程度上限制了其在实际应用中的规模化发展
[0038]与现有技术相比,本发明具有以下显著优点:通过稳定负载PCN-WO3异质结可以提高复合材料的光催化性能,增强对于染料污染物的光降解和微生物污染物的杀灭效率;PCN-WO3复合结构也可以提高复合材料的光热性能,增强其对于微塑料的吸附与沉积能力,同时提高微生物杀灭活性;通过控制PCN-WO3异质结的添加量,调控复合材料的孔道结构与尺寸大小,优化其对于水体污染物的吸附与光催化降解效率。
Smart Images

Figure CN122786993A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of wastewater treatment and environmental remediation technology, specifically to a wastewater purification composite material with PCN-WO3 heterostructures supported on loofah sponge and its preparation method. Background Technology
[0002] Water is indispensable to life on Earth, playing a crucial role in the integrity of ecosystems and the sustainable development of humankind. In recent years, with economic development and rapid industrialization and urbanization, water pollution has become increasingly serious. Developing new materials and technologies for wastewater treatment has become an urgent priority.
[0003] Among the various technologies researched to address water pollution, photocatalytic solar energy conversion technology is receiving increasing attention due to its enormous potential in tackling environmental problems. Graphitic carbon nitride (g-C3N4), a typical semiconductor photocatalyst, is widely used due to its non-toxicity and ease of preparation. However, pure-phase g-C3N4 suffers from inherent defects such as poor light absorption, insufficient active sites, and rapid recombination rates of photogenerated carriers (Nano Materials Science, 2025, 7: 145-168). Research has shown that by constructing heterojunctions by combining multiple semiconductor materials, the light absorption range of photocatalytic materials can be broadened, and the rapid recombination of electron-hole pairs can be suppressed, thereby improving their photocatalytic efficiency (Chemical Reviews, 2016, 116, 7159-7329). Furthermore, heterojunctions with photothermal properties can endow composite materials with photothermal properties, enhancing their ability to degrade pollutants and promoting the adsorption and deposition of microplastic pollutants. Based on this, the present invention constructs a stable heterojunction structure by in-situ combining two photothermally active semiconductor materials, g-C3N4 and WO3. This structure not only endows the material with excellent photocatalytic activity but also further enhances its photothermal performance, thus demonstrating significant advantages in improving the efficiency of water pollutant treatment.
[0004] It is worth noting that porous materials have shown significant application potential in the adsorption and removal of pollutants in water bodies. However, artificially synthesized porous materials generally suffer from high synthesis costs, and their preparation processes often rely on organic solvents and complex techniques, resulting in poor environmental friendliness and failing to meet the demands of green and sustainable development. In contrast, natural plant-based porous materials, such as loofah sponges, exhibit good application advantages and development prospects in the field of adsorption and separation due to their naturally formed porous physical structure and chemical composition that combines hydrophilic and oleophilic properties. However, the pore morphology, pore size distribution, and structural regularity of natural plant porous materials are difficult to precisely control, which to some extent limits their large-scale development in practical applications.
[0005] Based on this, this invention uses natural loofah sponge as a three-dimensional porous carrier and selects 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and N-hydroxysuccinimide (NHS) as crosslinking activation systems. Through the activation coupling reaction between carboxyl and amino groups, chemically stable amide bonds are generated. The PCN-WO3 heterostructure constructed from porous g-C3N4 and WO3 is stably loaded onto the surface of the loofah sponge pore structure, successfully preparing a loofah sponge-PCN-WO3 composite material. By controlling the amount of PCN-WO3 heterostructure added, the pore structure and size of the loofah sponge-PCN-WO3 composite material can be precisely controlled, optimizing its adsorption and photocatalytic degradation efficiency for water pollutants. Summary of the Invention
[0006] The first objective of this invention is to provide a method for preparing a wastewater purification composite material with PCN-WO3 heterojunction supported on loofah sponge. The second objective of this invention is to provide a wastewater purification composite material obtained by the method. The third objective of this invention is to provide applications of the wastewater purification composite material.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] A method for preparing a wastewater purification composite material supported on loofah sponge and PCN-WO3 heterostructures includes the following steps:
[0009] S1: Preparation of loofah sponge matrix material;
[0010] S2: Prepare porous g-C3N4, denoted as PCN;
[0011] S3: Preparation of PCN-WO3 heterojunction;
[0012] S4: The PCN-WO3 heterojunction is reacted with the loofah matrix material to obtain a wastewater purification composite material with PCN-WO3 heterojunction supported by loofah.
[0013] Furthermore, step S1 includes:
[0014] S1-1: Take natural loofah sponge, wash it with water, then wash it with anhydrous ethanol under reflux and dry it;
[0015] S1-2: Add NaOH solution to the loofah sponge treated in step S1-1, heat and stir to react, then wash thoroughly with hot water and dry.
[0016] S1-3: Add H2O2 solution to the loofah sponge treated in step S1-2, adjust the pH to be strongly alkaline, heat and stir to react, then wash thoroughly with water and dry.
[0017] S1-4: Add HCl solution to the loofah sponge treated in step S1-3, stir at room temperature, then wash with water until neutral, and then dry to obtain the loofah sponge matrix material.
[0018] Furthermore, in step S1-1, the size of the natural loofah sponge is 1~3cm×1~3cm×1~3cm, the amount of anhydrous ethanol used is 10~50ml, and the reflux washing time is 1~6h; in step S1-2, the amount of NaOH solution used is 10~50ml, the concentration of the NaOH solution is 1~4wt%, the temperature of the heating and stirring reaction is 50~90℃, and the time of the heating and stirring reaction is 2~6h; in step S1-3, the amount of H2O2 solution used is 10~50ml, the concentration of the H2O2 solution is 3wt%, the temperature of the heating and stirring reaction is 60~90℃, and the time of the heating and stirring reaction is 0.5~2h; in step S1-4, the amount of HCl solution used is 10~50ml, the concentration of the HCl solution is 0.05~2M, and the stirring time at room temperature is 10~40min.
[0019] Furthermore, step S2 includes:
[0020] S2-1: Mix urea and dicyandiamine and grind them using a ball mill to obtain a mixture;
[0021] S2-2: Transfer the mixture from step S2-1 to a muffle furnace and calcine it in an air atmosphere to obtain porous g-C3N4, denoted as PCN.
[0022] Furthermore, in step S2-1, the mass ratio of urea to dicyandiamine is 1~3:3~1, and the grinding time is 1~4h; in step S2-2, the calcination temperature is 400~600℃, and the calcination time is 3~6h.
[0023] Furthermore, step S3 includes:
[0024] S3-1: Mix Na2WO4·2H2O with water and stir at room temperature. Then, while stirring, add dropwise a mixture of hydrochloric acid and water to obtain a mixed solution.
[0025] S3-2: Add C2H8N2O4·H2O to the mixed solution in step S3-1, stir at room temperature, then add water and continue stirring, then add PCN and stir evenly to obtain a mixture;
[0026] S3-3: Transfer the mixture from step S3-2 into a high-pressure reactor for hydrothermal reaction, centrifuge to separate the solid product, wash with water and dry to obtain PCN-WO3 heterojunction.
[0027] Furthermore, in step S3-1, the ratio of Na2WO4·2H2O to water is 0.1~0.3g:10~40ml, the stirring time at room temperature is 10~20min, the amount of the mixture added is 8~15ml, the concentration of HCl in the mixture is 10~30wt%, and the addition time is 0.5~2h; in step S3-2, the amount of C2H8N2O4·H2O is 0.3~0.6g, the amount of water is 25~50ml, and the amount of PCN is 0.05~0.2g; in step S3-3, the temperature of the hydrothermal reaction is 70~120℃, and the time of the hydrothermal reaction is 4~8h.
[0028] Further, step S4 includes: dispersing the PCN-WO3 heterojunction in MES buffer, then adding EDC, NHS and loofah matrix material in sequence, stirring the reaction at room temperature, taking out the reacted loofah matrix material, washing it thoroughly with water, and drying it to obtain a wastewater purification composite material of loofah loaded with PCN-WO3 heterojunction.
[0029] Furthermore, in step S4, the ratio of PCN-WO3 to MES buffer is 0.6~1.5g:25~40ml, the pH of the MES buffer is 5.0~6.5, the ratio of EDC, NHS and loofah matrix material is 0.2~0.5g:0.1~0.3g:0.5~2g, and the stirring reaction time at room temperature is 6~18h.
[0030] A wastewater purification composite material supported on loofah sponge and PCN-WO3 heterostructures, wherein the wastewater purification composite material is prepared by the above-described preparation method.
[0031] The above-mentioned application of the wastewater purification composite material of loofah sponge supported on PCN-WO3 heterostructures is one or more of the following applications:
[0032] (1) Application in wastewater treatment;
[0033] (2) Application in the degradation of organic pollutants;
[0034] (3) Application in the preparation of antibacterial materials;
[0035] (4) Application in the adsorption and removal of microplastics.
[0036] Furthermore, the wastewater purification composite material has a porous structure with a relative porosity of 70% to 85%; the size of the PCN is 2-20 μm, and the size of the WO3 nanocrystals loaded on its surface is 50-200 nm.
[0037] The porous structure of wastewater purification composite materials is beneficial for the adsorption and photocatalytic degradation of water pollutants. The heterojunction formed by porous g-C3N4 (PCN) and WO3 (PCN-WO3) can improve the photocatalytic activity of the composite material, enhancing its degradation capacity for water pollutants. Furthermore, the heterojunction can also improve the photothermal properties of the composite material, enhancing its adsorption and deposition capacity for microplastics. By controlling the amount of PCN-WO3 added, the pore size of the loofah itself can be adjusted, optimizing its adsorption and photocatalytic degradation effects on water pollutants.
[0038] Compared with existing technologies, the present invention has the following significant advantages: by stably loading PCN-WO3 heterojunctions, the photocatalytic performance of the composite material can be improved, enhancing the photodegradation efficiency of dye pollutants and the killing efficiency of microbial pollutants; the PCN-WO3 composite structure can also improve the photothermal performance of the composite material, enhancing its adsorption and deposition capacity for microplastics, while improving its microbial killing activity; by controlling the amount of PCN-WO3 heterojunctions added, the pore structure and size of the composite material can be regulated, optimizing its adsorption and photocatalytic degradation efficiency for water pollutants. Attached Figure Description
[0039] Figure 1 The image shows the physical morphology of the loofah sponge-PCN-WO3 prepared in Example 1.
[0040] Figure 2 Scanning electron microscope images of (a) PCN, (b) PCN-WO3 and (c) loofah sponge-PCN-WO3 prepared in Example 1.
[0041] Figure 3 The X-ray powder diffraction pattern of PCN-WO3 prepared in Example 1.
[0042] Figure 4 The ROS release kinetic curves for each group of samples are shown.
[0043] Figure 5 The photothermal temperature curves for each group of samples are shown.
[0044] Figure 6 The dye degradation kinetic curves for each group of samples are shown.
[0045] Figure 7 The adsorption kinetics curves of microplastics for each group of samples are shown. Detailed Implementation
[0046] The technical solution of the present invention will be described in detail below with reference to the embodiments.
[0047] Example 1:
[0048] This embodiment provides a method for preparing a wastewater purification composite material supported on loofah sponge and PCN-WO3 heterostructures, comprising the following steps:
[0049] S1: Preparation of loofah sponge matrix material
[0050] S1-1: Take a natural loofah sponge with a size of 1cm×1cm×1cm, wash the surface impurities with deionized water, then wash it with 20ml of anhydrous ethanol at 80℃ for 2h, and then dry it in an oven at 60℃ until constant weight.
[0051] S1-2: Add 20 ml of 2 wt% NaOH solution to the loofah sponge treated in step S1-1, stir and react at 70°C for 4 h, then wash thoroughly with hot deionized water at 80°C, and dry in an oven at 60°C until constant weight.
[0052] S1-3: Add 20 ml of 3 wt% H2O2 solution to the loofah sponge treated in step S1-2, adjust the pH to 11-12 with NaOH, stir and react at 80℃ for 1 h, then wash thoroughly with deionized water and dry in a 60℃ oven to constant weight.
[0053] S1-4: Add 20 ml of 0.1 M HCl solution to the loofah sponge treated in step S1-3, stir at room temperature for 20 min, then wash with deionized water until neutral, and then dry in a 60 ℃ oven to constant weight to obtain the loofah sponge matrix material.
[0054] S2: Preparation of porous g-C3N4 (PCN)
[0055] S2-1: Urea and dicyandiamine are mixed at a mass ratio of 3:1 and ground in a ball mill for 2 hours to obtain a mixture. During grinding, φ3mm stainless steel grinding balls are used, and the grinding jar rotates at 320 rpm.
[0056] S2-2: Transfer the mixture from step S2-1 to a muffle furnace and calcine it at 530°C for 4 hours in an air atmosphere to obtain porous g-C3N4, denoted as PCN.
[0057] S3: Preparation of PCN-WO3
[0058] S3-1: Mix 0.23g Na2WO4·2H2O with 30ml deionized water and stir at room temperature for 15min. Then, while stirring, add dropwise a mixture of 2.8ml hydrochloric acid and 7.9ml deionized water. The entire addition process takes 1h to obtain a mixed solution.
[0059] S3-2: Add 0.5g C2H8N2O4·H2O to the mixed solution in step S3-1, stir at room temperature for 30min, then add 35ml deionized water and continue stirring for 15min, then add 0.1g PCN and stir evenly to obtain the mixture.
[0060] S3-3: Transfer the mixture from step S3-2 into a high-pressure reactor and react at 100°C for 5 hours. Centrifuge to separate the solid product, wash with deionized water and dry in an oven at 60°C for 24 hours to obtain a heterojunction formed by in-situ growth of WO3 nanocrystals on the PCN surface, denoted as PCN-WO3.
[0061] S4: Preparation of loofah sponge-PCN-WO3
[0062] 1 g of PCN-WO3 was dispersed in 30 ml of MES buffer (50 mM, pH=5.5), followed by the addition of EDC (0.3834 g, 2 mmol), NHS (0.1151 g, 1 mmol), and 1 g of the loofah matrix material prepared in step S1. The mixture was stirred at room temperature for 12 h. The reacted loofah matrix material was then removed, thoroughly washed with deionized water, and dried in a 60 °C oven to constant weight to obtain a wastewater purification composite material of loofah-supported PCN-WO3 heterojunctions, denoted as loofah-PCN-WO3. The actual product is shown below. Figure 1 As shown.
[0063] The microstructure of PCN, PCN-WO3, and loofah sponge-PCN-WO3 prepared in Example 1 was characterized, and the results are shown in [Figure 1]. Figure 2 .like Figure 2 As shown in Figure a, the PCN prepared by mechanical grinding and high-temperature calcination exhibits a typical g-C3N4 layered structure with a size of approximately 5 μm. Simultaneously, the surface of the layered structure contains numerous pores. Furthermore, a PCN-WO3 heterojunction was obtained by stably combining WO3 nanocrystals with PCN through in-situ synthesis. Figure 2 As shown in b, WO3 nanocrystals are abundantly loaded on the PCN surface, with a particle size of approximately 100 nm. Furthermore, the crystal structure of the PCN-WO3 heterojunction was examined using X-ray powder diffraction (XRD), and the diffraction peaks matched well with standard spectral peaks, confirming successful synthesis. Figure 3 Furthermore, EDC and NHS were used as crosslinking agents to stably load PCN-WO3 onto the loofah matrix material. Figure 2 c shows that PCN-WO3 is dispersed on the surface of the loofah matrix structure, and the dispersion is relatively uniform with no obvious agglomeration.
[0064] Example 2:
[0065] This embodiment provides a method for preparing a wastewater purification composite material with PCN-WO3 heterojunction supported on loofah sponge. The steps are roughly the same as those in Example 1, except that the amount of PCN-WO3 used in step S4 is 0.8g.
[0066] Example 3:
[0067] This embodiment provides a method for preparing a wastewater purification composite material with PCN-WO3 heterojunction supported on loofah sponge. The steps are roughly the same as those in Example 1, except that the amount of PCN-WO3 used in step S4 is 1.2g.
[0068] Comparative Example 1:
[0069] This comparative example provides a method for preparing a loofah sponge matrix material, the steps of which are the same as step S1 in Example 1.
[0070] Comparative Example 2:
[0071] This comparative example provides a method for preparing a wastewater purification composite material supported on loofah sponge and PCN, comprising the following steps:
[0072] S1: Preparation of loofah sponge matrix material
[0073] Same as step S1 in Example 1;
[0074] S2: Preparation of porous g-C3N4 (PCN)
[0075] Same as step S2 in Example 1;
[0076] S3: Preparation of loofah sponge-PCN
[0077] 1 g of PCN was dispersed in 30 ml of MES buffer (pH=5.5, 50 mM), followed by the addition of EDC (0.3834 g, 2 mmol), NHS (0.1151 g, 1 mmol), and 1 g of the loofah matrix material prepared in step S1. The mixture was stirred at room temperature for 12 h. The reacted loofah matrix material was then removed, thoroughly washed with deionized water, and dried in a 60 °C oven to constant weight to obtain the loofah-loaded PCN wastewater purification composite material, denoted as loofah-PCN.
[0078] Comparative Example 3:
[0079] This comparative example provides a method for preparing a wastewater purification composite material supported on loofah sponge and WO3, comprising the following steps:
[0080] S1: Preparation of loofah sponge matrix material
[0081] Same as step S1 in Example 1;
[0082] S2: Preparation of loofah sponge-WO3
[0083] S2-1: Mix 0.23g Na2WO4·2H2O with 30ml deionized water and stir at room temperature for 15min. Then, while stirring, add dropwise a mixture of 2.8ml hydrochloric acid and 7.9ml deionized water. The entire addition process takes 1h to obtain a mixed solution.
[0084] S2-2: Add 0.5g of C2H8N2O4·H2O to the mixed solution in step S2-1, stir at room temperature for 30min, then add 35ml of deionized water and continue stirring for 15min, then add 1g of the loofah matrix material obtained in step S1 and stir evenly to obtain a mixture.
[0085] S2-3: Transfer the mixture from step S2-2 into a high-pressure reactor and react at 100°C for 5 hours. Centrifuge to separate the product, wash with deionized water and dry at 60°C for 24 hours to obtain a composite material formed by in-situ growth of WO3 nanocrystals on the surface of loofah sponge, namely the wastewater purification composite material of loofah sponge loaded with WO3, denoted as loofah sponge-WO3.
[0086] The properties of the materials prepared in Examples 1-3 and Comparative Examples 1-3 were tested:
[0087] 1. ROS release kinetics detection:
[0088] Using 1,3-diphenylisobenzofuran (DPBF) as a ROS scavenger, the ROS yield of each group of samples (Examples 1, 2, 3 and Comparative Examples 1, 2, and 3) was evaluated by detecting the absorption peak intensity at 410 nm when irradiated with a xenon lamp (30 W) at room temperature.
[0089] Figure 4 Line graphs showing the DPBF absorption peak intensity for each group of samples (Examples 1, 2, 3, and Comparative Examples 1, 2, and 3). Figure 4 As shown, compared to Comparative Example 1, the DPBF absorption peak intensity values of Examples 1, 2, 3, Comparative Example 2, and 3 decreased significantly, demonstrating their significant ROS production capacity. Compared to Comparative Examples 2-3, the ROS yield of Examples 1-3 increased, proving that the design of the PCN-WO3 heterojunction can enhance the photocatalytic activity of the composite material, and the ROS yield of the loofah-PCN-WO3 composite material increased with the increase of PCN-WO3 loading.
[0090] 2. Photothermal performance testing:
[0091] Each group of samples (Examples 1, 2, 3 and Comparative Examples 1, 2, 3) was placed in pure water and irradiated with a xenon lamp (30W) at room temperature. The temperature changes were recorded using a thermocouple thermometer.
[0092] Figure 5 Line graphs showing the temperature-time changes for each group of samples (Examples 1, 2, 3, and Comparative Examples 1, 2, and 3). Figure 5 As shown, the temperature changes in Examples 1, 2, 3, Comparative Example 2, and Comparative Example 3 are quite significant, with the highest temperature reaching ~54℃. It is noteworthy that Examples 1-3 all show increased photothermal temperatures compared to Comparative Examples 2-3, demonstrating that the loading of the PCN-WO3 heterojunction can improve the photothermal performance of the composite material. Furthermore, with increasing PCN-WO3 loading, the photothermal activity of the loofah-PCN-WO3 composite material increases.
[0093] 3. Porosity testing:
[0094] The porosity of each group of samples (Examples 1, 2, and 3, and Comparative Examples 1, 2, and 3) was evaluated using the water displacement method (specific method reference: Archimedes revisited: computer-assisted microvolumetric modification of the liquid displacement method for porosity measurement of highly porous light materials, Analytical Methods, 2014, 6, 4396-4401). As shown in Table 1, compared with Comparative Example 1, the porosity of Comparative Examples 2-3 and Examples 1-3 all decreased. Among them, the porosity of the loofah-PCN-WO3 composite material decreased more significantly, all below 80%. With the increase of PCN-WO3 loading, the porosity of the loofah-PCN-WO3 composite material decreased. This moderate decrease in porosity may be beneficial to increasing the surface functional group density, which has certain potential for improving the degradation and adsorption efficiency of porous composite materials for water pollutants.
[0095] Table 1. Relative porosity of Examples 1-3 and Comparative Examples 1-3 of the present invention
[0096]
[0097] 4. Dye degradation experiment:
[0098] Rhodamine B (RhB) was used as a model organic pollutant for degradation experiments. Materials (10 mg) prepared in Examples 1, 2, and 3, and Comparative Examples 1, 2, and 3 were placed in 5 ml of a 20 mg / L Rhodamine aqueous solution and irradiated with a xenon lamp (30W) for 10 min at room temperature, with samples taken every 2 min. The absorbance of the solution was measured at the maximum absorption wavelength of Rhodamine B (554 nm) using a UV-Vis spectrophotometer. RhB standard solutions with concentrations of 2, 5, 10, 15, and 20 mg / L were prepared, and their absorbance was measured at 554 nm using a UV-Vis spectrophotometer to construct a standard curve for quantitative analysis of RhB degradation. The sample absorbance was converted to the corresponding actual Rhodamine B concentration based on the standard curve. The C / C0 ratio was used to characterize the relative residual rate of Rhodamine B; where C0 is the initial concentration of Rhodamine B solution in the degradation experiment, and C is the converted concentration of Rhodamine B solution at the corresponding sampling time point.
[0099] Figure 6 The absorption peak intensity variation curves for each group of samples (Examples 1, 2, 3, and Comparative Examples 1, 2, and 3) for the photocatalytic degradation process of Rhodamine B are shown. Figure 6 As shown, compared to Comparative Example 1, the absorption peak intensity values of Rhodamine B in Examples 1, 2, 3, Comparative Example 2, and 3 decreased significantly, demonstrating its significant photocatalytic degradation ability. The degradation efficiency of Rhodamine B for each group of samples corresponded to its ROS yield. With the increase of PCN-WO3 loading, the photocatalytic dye degradation activity of the loofah-PCN-WO3 composite material was enhanced, further proving that the design of the PCN-WO3 heterojunction has a promoting effect on improving the photocatalytic activity of the composite material.
[0100] 5. Antibacterial test:
[0101] Escherichia coli and Staphylococcus aureus were used as experimental strains in the antibacterial experiment. The revived bacteria were placed in liquid culture medium and incubated overnight on a shaker at 37°C. Materials (10 mg) prepared in Examples 1, 2, and 3, and Comparative Examples 1, 2, and 3 were placed in 12-well plates. 100 µL of bacterial suspension was added to the sample surface, and the plates were irradiated with a xenon lamp (30 W) for 10 min. Then, 1 mL of PBS was added to each sample, and after sonication, 50 µL of bacterial suspension was plated and incubated overnight on a shaker at 37°C. The number of bacterial colonies was then observed. The antibacterial effect of each sample was evaluated by calculating the relative bacterial survival rate.
[0102] As shown in Table 2, Examples 1-3 and Comparative Examples 2-3 all exhibited effective antibacterial effects against *Escherichia coli* and *Staphylococcus aureus*, with Examples 1-3 showing more significant antibacterial efficiency. Among them, Example 3 showed the best antibacterial effect (bacterial survival rate <5%), and the effect of the loofah-PCN-WO3 composite material increased with increasing PCN-WO3 loading. These experimental results are consistent with the ROS release and photothermal experiments, demonstrating that loading the PCN-WO3 heterojunction can increase the photocatalytic and photothermal activity of the composite material. Its high antibacterial efficiency is mainly attributed to the synergistic effect of photodynamic and photothermal antibacterial action.
[0103] Table 2. Relative bacterial survival rates of Examples 1-3 and Comparative Examples 1-3 of the present invention
[0104]
[0105] 6. Microplastic adsorption:
[0106] Polystyrene microspheres (particle size 0.05-0.1µm, 2.5% w / v) were selected as simulated microplastic pollutants. Materials (10 mg) prepared in Examples 1-3 and Comparative Examples 1-3 were placed in 5 ml of a 10 mg / L polystyrene microsphere solution and irradiated with a xenon lamp (30W) at room temperature. Samples were taken every 2 minutes for a total of 20 minutes. The absorbance of the solution was measured at the maximum absorption wavelength of 225 nm using a UV-Vis spectrophotometer. Standard solutions of polystyrene microspheres with concentrations of 2, 2.5, 3, 3.5, and 4 mg / L were prepared, and their absorbance was measured at 225 nm using a UV-Vis spectrophotometer to construct a standard curve for subsequent quantitative analysis. The sample absorbance was converted to the corresponding actual concentration of polystyrene microspheres based on the standard curve. The C / C0 ratio was used to characterize the relative residual rate of polystyrene microspheres; where C0 is the initial concentration of the polystyrene microsphere solution in the degradation experiment, and C is the concentration of the polystyrene microsphere solution obtained by conversion at the corresponding sampling time point.
[0107] like Figure 7 As shown, compared with Comparative Example 1, the microplastic removal rates of Examples 1-3 and Comparative Examples 2-3 were significantly improved. Among them, the loofah-PCN-WO3 composite material showed the most significant improvement in microplastic removal efficiency. It is noteworthy that when the loading of the PCN-WO3 heterojunction was 1.0 g, the relative porosity of the composite material was approximately 75%, at which point the microplastic removal efficiency was optimal. This may be related to the porosity of the loofah-PCN-WO3 composite material and the density of its surface functional groups. When the relative porosity of the loofah-PCN-WO3 composite material is ~75%, its surface pore size and surface functional group density are more conducive to the adsorption and removal of microplastics.
Claims
1. A method for preparing a wastewater purification composite material with PCN-WO3 heterojunction supported on loofah sponge, characterized in that: Includes the following steps: S1: Preparation of loofah sponge matrix material; S2: Prepare porous g-C3N4, denoted as PCN; S3: Preparation of PCN-WO3 heterojunction; S4: The PCN-WO3 heterojunction is reacted with the loofah matrix material to obtain a wastewater purification composite material with PCN-WO3 heterojunction supported by loofah.
2. The preparation method according to claim 1, characterized in that: Step S1 includes: S1-1: Take natural loofah sponge, wash it with water, then wash it with anhydrous ethanol under reflux and dry it; S1-2: Add NaOH solution to the loofah sponge treated in step S1-1, heat and stir to react, then wash thoroughly with hot water and dry. S1-3: Add H2O2 solution to the loofah sponge treated in step S1-2, adjust the pH to be strongly alkaline, heat and stir to react, then wash thoroughly with water and dry. S1-4: Add HCl solution to the loofah sponge treated in step S1-3, stir at room temperature, then wash with water until neutral, and then dry to obtain the loofah sponge matrix material.
3. The preparation method according to claim 2, characterized in that: In step S1-1, the size of the natural loofah sponge is 1~3cm×1~3cm×1~3cm, the amount of anhydrous ethanol used is 10~50ml, and the reflux washing time is 1~6h; In step S1-2, the amount of NaOH solution used is 10~50ml, the concentration of NaOH solution is 1~4wt%, the temperature of the heating and stirring reaction is 50~90℃, and the heating and stirring reaction time is 2~6h; In step S1-3, the amount of H2O2 solution used is 10~50ml, the concentration of H2O2 solution is 3wt%, the temperature of the heating and stirring reaction is 60~90℃, and the heating and stirring reaction time is 0.5~2h; In step S1-4, the amount of HCl solution used is 10~50ml, the concentration of HCl solution is 0.05~2M, and the stirring time at room temperature is 10~40min.
4. The preparation method according to claim 1, characterized in that: Step S2 includes: S2-1: Mix urea and dicyandiamine and grind them using a ball mill to obtain a mixture; S2-2: Transfer the mixture from step S2-1 to a muffle furnace and calcine it in an air atmosphere to obtain porous g-C3N4, denoted as PCN.
5. The preparation method according to claim 4, characterized in that: In step S2-1, the mass ratio of urea to dicyandiamine is 1~3:3~1, and the grinding time is 1~4h; in step S2-2, the calcination temperature is 400~600℃, and the calcination time is 3~6h.
6. The preparation method according to claim 1, characterized in that: Step S3 includes: S3-1: Mix Na2WO4·2H2O with water and stir at room temperature. Then, while stirring, add dropwise a mixture of hydrochloric acid and water to obtain a mixed solution. S3-2: Add C2H8N2O4·H2O to the mixed solution in step S3-1, stir at room temperature, then add water and continue stirring, then add PCN and stir evenly to obtain a mixture; S3-3: Transfer the mixture from step S3-2 into a high-pressure reactor for hydrothermal reaction, centrifuge to separate the solid product, wash with water and dry to obtain PCN-WO3 heterojunction.
7. The preparation method according to claim 6, characterized in that: In step S3-1, the ratio of Na2WO4·2H2O to water is 0.1~0.3g:10~40ml, the stirring time at room temperature is 10~20min, the amount of the mixture added is 8~15ml, the concentration of HCl in the mixture is 10~30wt%, and the addition time is 0.5~2h; in step S3-2, the amount of C2H8N2O4·H2O is 0.3~0.6g, the amount of water is 25~50ml, and the amount of PCN is 0.05~0.2g; in step S3-3, the temperature of the hydrothermal reaction is 70~120℃, and the time of the hydrothermal reaction is 4~8h.
8. The preparation method according to claim 1, characterized in that: Step S4 includes: dispersing the PCN-WO3 heterojunction in MES buffer, then adding EDC, NHS and loofah matrix material in sequence, stirring the reaction at room temperature, taking out the reacted loofah matrix material, washing it thoroughly with water, and drying it to obtain a wastewater purification composite material of loofah loaded with PCN-WO3 heterojunction.
9. The preparation method according to claim 8, characterized in that: In step S4, the ratio of PCN-WO3 to MES buffer is 0.6~1.5g:25~40ml, the pH of the MES buffer is 5.0~6.5, the ratio of EDC, NHS and loofah matrix material is 0.2~0.5g:0.1~0.3g:0.5~2g, and the stirring reaction time at room temperature is 6~18h.
10. An application of a wastewater purification composite material prepared by the method described in claim 1, characterized in that: The application can be any one or more of the following: (1) Application in wastewater treatment; (2) Application in the degradation of organic pollutants; (3) Application in the preparation of antibacterial materials; (4) Application in the adsorption and removal of microplastics.